OzoNews Volume XX - 15 November 2020 - United Nations Environment Programme (2021)
In this issue: 1. Kigali Amendment latest ratifications 2. OzonAction Virtual Side Events at MOP 32 3. Contingency meeting plans for 2020-2021: update 4. The seasonal ozone hole over Antarctica will remain active well into November 5. Survey Seeks Feedback on NatRef Trends in 2021 6. Call for Green Cooling Project Ideas 7. The Montreal Protocol an exemplary success 8. Algeria on the way to achieve its commitments under the Montreal Protocol 9. UNDP Moldova pledges for the use of environmentally friendly refrigerants, that do not deplete the ozone layer 10. EU seeks to phase out planet-warming refrigerants 11. National produces short guides to new refrigerants 12. Pacific Island Countries Gearing up to Enact HFC Licensing Systems 13. Workshop on good servicing practices for flammable refrigerants at Vava'u 14. UNEP Partners with ASHRAE and AUB on Policies and Codes in the Building Sector from the Montreal Protocol Perspective 15. US EPA to regulate most uses of carbon tetrachloride 16. Safety Alert: Online sales of Cool Penguin F-12 17. New state rules regulating methyl bromide use in log fumigation take effect